Methamphetamine and Modulation Functionality of the Prelimbic Cortex for Developing a Possible Treatment of Alzheimer’s Disease in an Animal Model - Shyu, Bai-Chuang; Gao, Zhi-Yue; Wu, José Jiun-Shian; He, Alan Bo Han; Cheng, Cai-N; Huang, Andrew Chih Wei (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) is a progressive neurodegenerative condition that causes cognitive impairment and other neuropsychiatric symptoms. Previously, little research has thus far investigated whether methamphetamine (MAMPH) can enhance cognitive function or ameliorate AD symptoms. This study examined whether a low dose of MAMPH can induce conditioned taste aversion (CTA) learning, or can increase plasma corticosterone levels, neural activity, and neural plasticity in the medial prefrontal cortex (mPFC) (responsible for cognitive function), the nucleus accumbens (NAc) and the amygdala (related to rewarding and aversive emotion), and the hippocampus (responsible for spatial learning). Furthermore, the excitations or lesions of the prelimbic cortex (PrL) can affect MAMPH-induced CTA learning, plasma corticosterone levels, and neural activity or plasticity in the mPFC (i.e., PrL, infralimbic cortex [IL], cingulate cortex 1 [Cg1]), the NAc, the amygdala (i.e., basolateral amygdala [BLA] and central amygdala [CeA]), and the hippocampus (i.e., CA1, CA2, CA3, and dentate gyrus [DG]). In the experimental procedure, the rats were administered either saline or NMDA solutions, which were injected into the PrL to excite or destroy PrL neurons. Additionally, rats received 0.1% saccharin solution for 15 min, followed by intraperitoneal injections of either normal saline or 1 mg/kg MAMPH to induce CTA. A one-way ANOVA was performed to analyze the effects of saccharin intake on CTA, plasma corticosterone levels, and the expression of c-Fos and p-ERK. The results showed that the MAMPH induced CTA learning and increased plasma corticosterone levels. The mPFC, and particularly the PrL and IL and the DG of the hippocampus, appeared to show increased neural activity in c-Fos expression or neural plasticity in p-ERK expression. The excitation of the PrL neurons upregulated neural activity in c-Fos expression and neural plasticity in p-ERK expression in the PrL and IL. In summary, MAMPH may be able to improve cognitive and executive function in the brain and reduce AD symptoms. Moreover, the excitatory modulation of the PrL with MAMPH administration can facilitate MAMPH-induced neural activity and plasticity in the PrL and IL of the mPFC. The present data provide clinical implications for developing a possible treatment for AD in an animal model.